Simultaneous central retinal vein and cilioretinal artery occlusion in a young female patient with progestin-only oral contraceptive use: a case report - Sardar Noman Qayyum; Risha Naeem; Faraz Azhar; Gulmeena Aziz Khan; Tehreem Zubair; Samim Noori (Journal of Medical Case Reports)
Abstract Background Central retinal vein occlusion and cilioretinal artery occlusion are rare but serious ocular conditions that can lead to significant visual impairment. While few cases of central retinal vein occlusion and cilioretinal artery occlusion have been individually reported, concurrent occlusion of both vessels is extremely rare, particularly in younger patients without traditional vascular risk factors. We present the first reported case of simultaneous central retinal vein occlusion and cilioretinal artery occlusion in a young female patient associated with short-term use of progestin-only oral contraceptives (OCPs). Case presentation A 28-year-old Pakistani female patient presented with sudden, painless vision loss in the left eye, 3 hours prior to her arrival at the ophthalmology clinic. Visual acuity in the affected eye was limited to counting fingers at a distance of 0.5 feet, with a best-corrected visual acuity of 6/6 in the right eye. Fundoscopic examination revealed optic disc edema, preretinal hemorrhages, venous dilation, and cotton wool spots consistent with central retinal vein occlusion, alongside ischemic changes in the foveal region suggestive of cilioretinal artery occlusion. On the basis of clinical examination, fundus fluorescein angiography, and optical coherence tomography findings, the patient was diagnosed with concurrent central retinal vein occlusion and cilioretinal artery occlusion. Systemic workup to rule out thrombophilia and other vascular risks was negative. She was treated with acetazolamide, aspirin, and ocular massage, alongside a dorzolamide-timolol combination for intraocular pressure control. Six weeks later, panretinal photocoagulation was performed to prevent neovascular complications. Conclusions This case highlights the rare presentation of simultaneous central retinal vein occlusion and cilioretinal artery occlusion, likely precipitated by short-term progestin-only OCP use in a young female. The absence of other vascular risk factors emphasizes the potential thrombotic risk associated with hormonal contraception, even in brief courses. Careful consideration should be given to contraceptive choice, and ophthalmologic monitoring is recommended for early detection and intervention in at-risk patients.